Progranulin Reduction Is Associated With Increased Tau Phosphorylation in P301L Tau Transgenic Mice. Issue 2 (February 2015) - Hosokawa, Masato; Arai, Tetsuaki; Masuda-Suzukake, Masami; Kondo, Hiromi; Matsuwaki, Takashi; Nishihara, Masugi; Hasegawa, Masato; Akiyama, Haruhiko
<x xml:space="preserve">Abstract</x> Abstract Granulin (GRN) mutations have been identified in familial frontotemporal lobar degeneration patients with ubiquitin pathology. GRN transcript haploinsufficiency is proposed as a disease mechanism that leads to the loss of functional progranulin (PGRN) protein. Thus, these mutations are strongly involved in frontotemporal lobar degeneration pathogenesis. Moreover, recent findings indicate that GRN mutations are associated with other neurodegenerative disorders with tau pathology, including Alzheimer disease and corticobasal degeneration. To investigate the potential influence of a decline in PGRN protein on tau accumulation, P301L tau transgenic mice were interbred with GRN-deficient mice, producing P301L tau transgenic mice harboring the GRN hemizygote. Brains were collected from 13- and 19-month-old mice, and sequential extraction of proteins, immunoblotting, and immunohistochemical analyses were performed. Immunoblotting analysis revealed that tau phosphorylation was accelerated in the Tris-saline soluble fraction of 13-month-old and in the sarkosyl-insoluble fraction of 19-month-old P301L tau/GRN hemizygotes compared with those in fractions from P301L tau transgenic mice. Activity of cyclin-dependent kinases was also upregulated in the brains of P301L tau/GRN hemizygote mice. Although the mechanisms involved in these findings remain unknown, our data suggest that a reduction in PGRN protein might contribute to phosphorylation and intraneuronal accumulation of tau.